The Influence of Competence, Compensation, and Commitment on the Performance of Military Polytechnic Army Teachers - Widiyoko Pambudi; Ferikawita Magdalena Sembiring (Komando (Kompetensi Manajemen dan Organisasi): Bisnis dan Pertahanan, 2025)
Competence, Compensation and Commitment are important factors in improving Gumil performance so that it influences the fluency of the teaching and learning process in educational institutions, especially the Army Polytechnic. The aims of this study are: i) To analyze the effect of Competence on the Performance of the Army Polytechnic Gumil: ii) To analyze the effect of Compensation on the Performance of the Army Polytechnic Gumil; iii) To analyze the effect of Commitment on the Performance of the Army Polytechnic Gumil; iv) To analyze the influence of Compensation, Compensation and Commitment simultaneously on the Performance of the Army Polytechnic Gumil. This study uses a survey system by distributing questionnaires to predetermined respondents. This type of research uses explanatory research. The population of this study is 74 Gumil people who teach at the Army Polytechnic. The sample in this study is the entire population of 74 people or a saturated sample. The statistical analysis used in this study is Multiple Linear Regression with the help of SPSS Version 25. The results of this study indicate that: i) Competence influences the performance of Army Polytechnic Gumil; ii) Compensation has no effect on the Performance of the Army Polytechnic Gumil; iii) Commitment influences the performance of the Army Polytechnic Gumil; iv). Competence, Compensation and Commitment have a Simultaneous effect on the Performance of the Army Polytechnic Gumil.